Phytochemical study and subacute toxicity in vivo evaluation of Phyllanthus odontadenius (Phyllanthaceae) aqueous extracts - MUANGU-KABI Oscar NSENDO; Rufin Kikakedimau Nakweti; Makinutewa Alain Mbozo; Kalulu-Muzele TABA; Koto-Te-Nyiwa Ngbolua; NDIKU Sébastien LUYINDULA (Orapuh Journal)
Introduction